ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BESARNYA PENGAMBILAN KREDIT PADA PT PEGADAIAN CABANG NGANJUK - Apriliana, Lia; Irmayanti, Elis; Afandi, Tjetjep Yusuf (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research is motivated by the results of observations from researchers to find out what are the factors that influence the amount of credit taking at PT Pegadaian Nganjuk Branch. The purpose of this study was to determine: (1) to determine the factor of the level of income of the people of Tanjunganom District, (2) to determine the amount of credit taking compared to the ratio of the estimated value at PT Pegadaian, (3) to find out why the credit repayment period was too long at PT. Pegadaian. This study uses a qualitative approach with research subjects Tanjunganom District Community. This research was carried out by distributing in-depth interviews in order to explore what factors could make a lot of people take credit at PT Pegadaian. So, the level of income is always up and down so that the ratio of the estimated value is 0.45% for gold and 0.65% for non-gold, while the minimum payback period is 4 months and a maximum of 3 years